2011
DOI: 10.4103/0256-4947.75778
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nucleophosmin and FMS-like tyrosine kinase-3 gene mutations in acute myeloid leukemia

Abstract: BACKGROUND AND OBJECTIVES:Nucleophosmin gene mutations are frequently reported in acute myeloid leukemia (AML) patients with normal karyotype, which is also frequently associated with internal tandem duplication mutations in the FMS-like tyrosine kinase-3 gene. We sought to detect the nucleophosmin and FMS-like tyrosine kinase-3 (FLT3) internal tandem duplication (ITD) mutations among Iranian patients with AML and to assess the relationship between these mutations and the subtypes of the disease.DESIGN AND SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(45 reference statements)
3
3
0
Order By: Relevance
“…This result was higher than previously reported findings. [37][38][39][40][41][42][43] However, our results are in accordance with other Egyptian (48.3%), 44 (45.8%) 45 and Iraqi (46.88%) 46 studies. These differences may be attributed to difference in method of detection, sample size, ethnic, racial, environmental, and geographical factors.…”
Section: Discussionsupporting
confidence: 80%
“…This result was higher than previously reported findings. [37][38][39][40][41][42][43] However, our results are in accordance with other Egyptian (48.3%), 44 (45.8%) 45 and Iraqi (46.88%) 46 studies. These differences may be attributed to difference in method of detection, sample size, ethnic, racial, environmental, and geographical factors.…”
Section: Discussionsupporting
confidence: 80%
“…The incidence of FLT3-ITD+ in the current study was 15.9%, which is obviously similar incidences having been previously reported in some studies (Table 5) (Elyamany et al, 2014;Aly et al, 2012;Pazhakh et al, 2011). Several studies observed a lower incidence of FLT3-ITD+ than in our study (Elyamany et al, 2014;Aly et al, 2012;Pazhakh et al, 2011;Ishfaq et al, 2002;Gari et al, 2008;Sheikhha et al, 2003). Various studies have detected a high occurrence of FLT3-ITD+ (Thiede et al, 2002;Xu et al, 2012;Wang et al, 2010;Al-tonbary et al, 2009;Suzuki et al, 2007;Wang et al, 2005;Auewarakul et al, 2005;Fröhling et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Adult studies have shown a prevalence of 25-30% for the FLT3-ITD+ in AML patients who have no cytogenetic abnormalities (Schnittger et al, 2002;Patnaik 2018;Griffith et al, 2004) and ~7% for FLT3-KTD point mutation of the activation loop domain (Bacher et al, 2008;Yamamoto et al, 2001;Kim 2010). The incidence of FLT3-ITD+ in the current study was 15.9%, which is obviously similar incidences having been previously reported in some studies (Table 5) (Elyamany et al, 2014;Aly et al, 2012;Pazhakh et al, 2011). Several studies observed a lower incidence of FLT3-ITD+ than in our study (Elyamany et al, 2014;Aly et al, 2012;Pazhakh et al, 2011;Ishfaq et al, 2002;Gari et al, 2008;Sheikhha et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…FLT3-ITD mutations (exon 14-15) were analysed on genomic DNA by PCR amplification as previously described [17]. In the absence of FLT3-ITD a fragment of 329 bp was detected in wild-type FLT3 gene whereas additional upper band (higher molecular weight band) was observed in cases with FLT3-ITD mutation (Fig.…”
Section: Detection Of Flt3 and Npm1 Mutationsmentioning
confidence: 99%